Jojoba: a potential industrial crop of Malaysia? / Zakaria Tajuddin - Tajuddin, Zakaria (Universiti Teknologi MARA Cawangan Pahang, 1993)
Jojoba has generated worldwide interest because its oil is an excellent substitutes for the industrially valuable sperm whale oil. Jojoba is being cultivated commercially or experimentally in widely different climatic conditions. The potential of jojoba as a future Malaysia's industrial crop will depend on further research and development. The purpose of this article is to compile the literature on jojoba and review its status as a potential oil crop. The article describes the distribution, cultural practices, reproduction, pest and diseases, harvesting, yield and uses of jojoba.